Lasang Lasallian - Carandang, Ernesto V. (Ernesto Villaluz); Sison-Buban, Rakki E. (Central Book Supply, Inc. for De La Salle University, 2011)
Filipino food offered by canteens located surrounding De La Salle University in the Philippines.